ATP binding by an F1Fo ATP synthase ε subunit is pH dependent, suggesting a diversity of ε subunit functional regulation in bacteria - Krah, Alexander; Vogelaar, Timothy; de Jong, Sam I.; Claridge, Jolyon K.; Bond, Peter J.; McMillan, Duncan G. G. (Frontiers in Molecular Biosciences, 2023)
It is a conjecture is the ε subunit regulates ATP hydrolytic function of the F1Fo ATP synthase in bacteria. This has been proposed by the ε subunit taking an extended conformation, with a terminal helix probing into the central architecture of the hexameric catalytic domain, preventing ATP hydrolysis. The ε subunit takes a contracted conformation when bound to ATP, thus would not interfere with catalysis. A recent crystallographic study has disputed this; the Caldalkalibacillus thermarum TA2.A1 F1Fo ATP synthase cannot natively hydrolyse ATP, yet studies have demonstrated that the loss of the ε subunit terminal helix results in an ATP synthase capable of ATP hydrolysis, supporting ε subunit function. Analysis of sequence and crystallographic data of the C. thermarum F1Fo ATP synthase revealed two unique histidine residues. Molecular dynamics simulations suggested that the protonation state of these residues may influence ATP binding site stability. Yet these residues lie outside the ATP/Mg2+ binding site of the ε subunit. We then probed the effect of pH on the ATP binding affinity of the ε subunit from the C. thermarum F1Fo ATP synthase at various physiologically relevant pH values, We showing binding affinity changes 5.4 fold between pH 7.0, where binding is weakest, to pH 8.5 where it is strongest. Since the C. thermarum cytoplasm is pH 8.0 when it grows optimally, this correlates to the ε subunit being down due to ATP/Mg2+ affinity, and not being involved in blocking ATP hydrolysis. Here, we have experimentally correlated that the pH of the bacterial cytoplasm is of critical importance for ε subunit ATP affinity regulated by second-shell residues thus the function of the ε subunit changes with growth conditions.